Penggunaan Toolspack Analysis Excel dalam pengolahan data pada guru-guru di Kabupaten Gowa - Muhammad Dinar; Rusli Rusli; Irwan Irwan; Hastuty Hastuty (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The use of Toolspack Anaysis excel in processing data is done in the form of training for mathematics teachers in Gowa district who are members of the MGMP group. The training was attended by 21 teachers who were carried out at SMAN 5 Tinggimoncong, Gowa Regency. The purpose of this training is for teachers to use the statistical package owned by Excel to process data. The results of the training show that the average ability of teachers to use statistics in the excel analysis toolspack package in processing data after training is better than before training